Colostomy Indications - Chifflet, Abel (Cirugía del Uruguay, 2020)
Years ago, a colostomy was an almost obligatory operation in most colon and rectal conditions, either as a single bypass operation or as part of a staged surgical treatment. Progress in colon surgery forces reconsideration of these indications.